STUDY MANAJEMEN PENERBITAN BUKU DI INDONESIA - Purnomo Ananto (Politeknik Negeri Media Kreatif, 2017)
Industry of Books has a strategic goal is not only to improve the welfare of the people involved, but also support the advancement of national education in particular in order to participate in the intellectual life of the nation. The industry has become one of the pillars in the transfer of science and technology, both within schools and colleges of education and in industrial processes. In this context the publishers editorial management has a strategic role to direct and manage so that these goals can be achieved. Relative to the researchers tried to capture how the actual process of publishing the book, particularly from the editorial management. To get a detailed description, the survey carried out activities of companies engaged in the industry of Books in Bandung. The application of this method is supported technically by using interviews and questionnaires. After that, apply a descriptive method of the editorial management books in Bandung. The editor of the book to the publisher in London in general, working with authors to improve the quality of the book. Editors often conduct a hearing with the author of the book material to be presented, ranging from the layout, content, up to finishing the manuscript. In addition, the editors perform field surveys, such as listening to and receive feedback from potential customers regarding the contents of the book as to what he wanted.